Inter-amphibian predation in the Early Cretaceous of China - Xing, Lida; Niu, Kecheng; Evans, Susan E. (Scientific reports, 2019)
For most fossil taxa, dietary inference relies primarily on indirect evidence from jaw morphology and the dentition. In rare cases, however, preserved gut contents provide direct evidence of feeding strategy and species interaction. This is important in the reconstruction of food webs and energy flow through ancient ecosystems. The Early Cretaceous Chinese Jehol Biota has yielded several such examples, with lizards, birds, small dinosaurs, and mammals as both predator and prey. Here we describe an Early Cretaceous fossil frog specimen, genus Genibatrachus , that contains an adult salamander within its body cavity. The salamander is attributed to the hynobiid-like genus Nuominerpeton . The salamander skeleton is complete and articulated, suggesting it was caught and swallowed shortly before the frog itself died and was buried.